Historia política de los discursos educativos Pueblos originarios y Estado en Bolivia, 1931-2010 - Oyarzo Varela, Cristina (Ariadna Ediciones, 2021)
In Bolivia, education was a major concern throughout the 20th century, as in much of Latin America. But in this country it acquired a specificity that marked the trajectories of the socio-political movements involved, as well as institutional responses generated by the State. This was largely due to the demographic and cultural weight of the indigenous peoples that inhabit the territory and the vitality of their social and political practices. The general objective of this research is to give an account of the trajectories of the discourses on the functions of education for indigenous peoples through the critical reading of materials produced from the self-ascribed enunciation as indigenous -individual and collective- and the enunciation of the State through the educational reforms of 1955, 1994 and 2010. The exploration will try to reveal the interrelations between these debates, the negotiations and the articulations generated.